Les effets du régime des feux : exemples pris dans le bassin méditerranéen - Trabaud L. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The influence of fire on ecosystems of the Mediterranean Basin is analysed through the fire regime: frequency, intensity, season. The timing and periodicity of fires are extremely important in the lives of plant communities as these factors affect plant survival, flowering and phytomass, whereas fire intensity affects the resistance of plants and seed germination. The size of the burned area is also an important ecological factor affecting recolonization. By destroying subterranean survival organs the depth of the burn influences the rate and type of recovery. Environmental factors play also a determining role.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)